Atypical Bilateral Posterior Semicircular Canalolithiasis – A Case Series - Ajay K Vats; Shreya Vats; Sudhir Kothari; Nishant Aswani (Annals of Indian Academy of Neurology)
Barany Society includes bilateral typical posterior semicircular canal benign paroxysmal positional vertigo (PSC-BPPV) in its classification of multicanal subtype. In the past decade, less-common and atypical subtypes of PSC-BPPV, like short-arm and non-ampullary arm posterior semicircular canalolithiasis, have emerged, requiring the conduct of conventional and auxiliary positional tests on both sides to uncover their bilaterality. Authors hereby report three atypical less-common subtypes of bilateral PSC-BPPV, discussing their clinicodemographic profiles, management by repositioning maneuvers and physical therapy, and follow up. Both Case 2 and Case 3 are precisely tri-canalolithiasis (bilateral ampullary arm posterior semicircular canalolithiasis with co-occurring right non-ampullary arm posterior semicircular canalolithiasis in Case 2 and bilateral short arm with co-occurring left ampullary arm posterior semicircular canalolithiasis in Case 3), which has not been reported previously in the literature. There has been only one previously reported case of bilateral non-ampullary arm semicircular canalolithiasis, and it is now observed in Case 1.